Administration of non-national immunization program vaccines for children under six in a rural county, Henan Province: Did costs matter? - Miaomiao Yin; Yuan Cao; Xiaolin Xu; Hanzhi Peng; Yu Wang; Qian Long (Human Vaccines & Immunotherapeutics)
This study aimed to investigate caregivers’ administration of non-National Immunization Program (NIP) vaccines in rural China, and examine health system, individual, and social determinants. A cross-sectional survey (n = 1051) was conducted from July to October in 2022 in a rural county of Henan Province. Caregivers of children under six who came to township health centers for child vaccination were interviewed. Cross-tabulation and multivariate logistic regressions were used to examine the administration rate and associated factors. Qualitative interviews were conducted with healthcare professionals (n = 4) and caregivers (Focus Group Discussions, n = 4) to understand local policies, routine practices, and caregivers’ experience with the administration of non-NIP vaccines. A framework approach was used to analyze qualitative data. Quantitative and qualitative data were integrated during the interpretation of the results. The administration rate for non-NIP vaccines remained low in rural Henan, 26.7% of children had not received any non-NIP vaccines, 43.5% had received 1–2 types, and around 30% had received 3–5 types. There were no significant differences in the administration of non-NIP vaccines between left-behind and non-left-behind children after adjusting for characteristics of children, caregivers, and households. Qualitative findings reflected that the high cost of non-NIP vaccines was a primary factor influencing caregivers’ vaccination decision. Poor communication between physicians and caregivers was another significant factor, which was caused by low retention of healthcare workers, a shortage of professionals, and insufficient financial incentives for physicians. This study enriches the evidence on non-NIP vaccination among rural children, particularly for the vulnerable group of left-behind children.